Parametric Capacitive Measuring Air Clearance Converter Between Rotor and Stator of Rotating Electric Cars - Hraniak, V. F.; Kukharchuk, V. V.; S. Sh. (Visnyk of Vinnytsia Politechnical Institute, 2020)
The paper substantiates that based on the considerations of ensuring the versatility and reducing the cost of construction of measuring the air gap between the rotor and stator of rotating electric machines, it is advisable to use measuring transducers of air gap in the value of the output DC voltage. Such a measuring transducer will allow you to implement a measuring instrument based on serial microcontrollers with built-in voltage ADC. It is shown that the most suitable for use in conjunction with electric machines in the process of their industrial operation are capacitive air gap sensors. However, due to the relatively low sensitivity of this class of primary measuring transducers, their use in conjunction with serial secondary transducers such as "capacitance - voltage" has serious limitations, exacerbated by the need to adapt the measuring instrument to a wide class of rotating electric machines with different nominal air values the clearance between the rotor and the stator. Given these circumstances, it was proposed to design a secondary measuring transducer type "capacitance-voltage", characterized by variable gain, relatively simple design and low value of additional error, which will solve the existing problem of matching the measuring signal between the sensor and the sensor existing analog-to-digital voltage converters, which are usually equipped with modern microcontrollers. A mathematical model of the proposed secondary measuring instrument obtained by further development of the Terentyev rectifier calculation method (monogram method) was developed, which allowed adapting it for calculation of rectifiers with low value of input supply voltage and small value of load currents. A mathematical model of the air gap measuring transducer between the rotor and the stator of rotating electric machines into voltage is obtained, which is a series connection of the capacitive air gap sensor and the proposed secondary measuring transducer of the "capacitance-voltage" type. The adequacy of the mathematical model was confirmed experimentally.